Pharmacological Inhibition of FAK-Pyk2 Pathway Protects Against Organ Damage and Prolongs the Survival of Septic Mice - Alves, Gustavo Ferreira; Aimaretti, Eleonora; Einaudi, Giacomo; Mastrocola, Raffaella; de Oliveira, Junior Garcia; Collotta, Debora; Porchietto, Elisa; Aragno, Manuela; Cifani, Carlo; Sordi, Regina; Thiemermann, Christoph; Fernandes, Daniel; et al. (Frontiers in Immunology, 2022)
Sepsis and septic shock are associated with high mortality and are considered one of the major public health concerns. The onset of sepsis is known as a hyper-inflammatory state that contributes to organ failure and mortality. Recent findings suggest a potential role of two non-receptor protein tyrosine kinases, namely Focal adhesion kinase (FAK) and Proline-rich tyrosine kinase 2 (Pyk2), in the inflammation associated with endometriosis, cancer, atherosclerosis and asthma. Here we investigate the role of FAK-Pyk2 in the pathogenesis of sepsis and the potential beneficial effects of the pharmacological modulation of this pathway by administering the potent reversible dual inhibitor of FAK and Pyk2, PF562271 (PF271) in a murine model of cecal ligation and puncture (CLP)-induced sepsis. Five-month-old male C57BL/6 mice underwent CLP or Sham surgery and one hour after the surgical procedure, mice were randomly assigned to receive PF271 (25 mg/kg, s.c.) or vehicle. Twenty-four hours after surgery, organs and plasma were collected for analyses. In another group of mice, survival rate was assessed every 12h over the subsequent 5 days. Experimental sepsis led to a systemic cytokine storm resulting in the formation of excessive amounts of both pro-inflammatory cytokines (TNF-α, IL-1β, IL-17 and IL-6) and the anti-inflammatory cytokine IL-10. The systemic inflammatory response was accompanied by high plasma levels of ALT, AST (liver injury), creatinine, (renal dysfunction) and lactate, as well as a high, clinical severity score. All parameters were attenuated following PF271 administration. Experimental sepsis induced an overactivation of FAK and Pyk2 in liver and kidney, which was associated to p38 MAPK activation, leading to increased expression/activation of several pro-inflammatory markers, including the NLRP3 inflammasome complex, the adhesion molecules ICAM-1, VCAM-1 and E-selectin and the enzyme NOS-2 and myeloperoxidase. Treatment with PF271 inhibited FAK-Pyk2 activation, thus blunting the inflammatory abnormalities orchestrated by sepsis. Finally, PF271 significantly prolonged the survival of mice subjected to CLP-sepsis. Taken together, our data show for the first time that the FAK-Pyk2 pathway contributes to sepsis-induced inflammation and organ injury/dysfunction and that the pharmacological modulation of this pathway may represents a new strategy for the treatment of sepsis.